Architecture - Behaviour - Properties Relationship In Star-Shaped MPA-PMMA And MPA-PS Hyper-Branched Copolymers - Rios Valer, Gabriel Bernardo (2019)
The molecular architecture of polymers is a crucial feature in the moment of think the relationship between properties and applications. The same polymer can present important differences according to its architecture and leads to different possible applications. In this paper, we describe the well preparation of hyperbranched copolymers based on bis (HydroxylMethyl) propionic acid polyester (MPA). The co-monomers introduced via atom transfer radical polymerization were methyl methacrylate (MMA) and styrene (St). In order to study the effect of confinement, linear PMMA and PSt have been prepared, and moreover different levels of branching of each polymer were prepared. The synthesised star PMPAPMMA and PMPA-PSt copolymers have been characterized and identified by infrared spectroscopy and nuclear magnetic resonance spectroscopy. Thermal transitions in solid state were studied using differential scanning calorimetry, and the thermal stability was evaluated by thermogravimetric analysis. Finally, solution properties have been evaluated thought Dynamic Light Scattering. Our results, obtained by a meticulous and systematic comparative study, showed a clear tendency between architectural level and thermal properties. Moreover, properties in solution revealed interesting response due to the modification of solvent nature.